Implementing Blue Ocean Leadership to Improve Productivity in Automotive Manufacturing - Abdurohman Abdurohman; Anita Maulina (Penerbit Goodwood, 2026)
Purpose: This study aims to analyse improvements in employee productivity through the application of the Blue Ocean Leadership method in an automotive manufacturing company. Research Methodology: This research employs a qualitative case study approach based on the Blue Ocean Leadership framework. Data were collected through in-depth interviews, direct observation, analysis of productivity performance indicators, descriptive statistical analysis, and mapping of management practices implemented at PT Enkei Marutoyo Painting Indonesia. Result: The findings indicate an increase in labour productivity, clearer role alignment, a reduction in non-value-adding managerial activities, higher levels of employee engagement, and more effective leadership practices following the implementation of Blue Ocean Leadership principles. Conclusions: The results demonstrate that Blue Ocean Leadership implementation across all leadership levels effectively bridges the gap between employees' potential and their actual performance, resulting in improved labor productivity, enhanced role clarity, increased employee engagement, and more effective leadership practices within the automotive manufacturing sector. Limitations: This study is limited to a single company, one specific department, and a defined observation period, which may restrict the generalizability of the findings. Contributions: This research contributes to studies on leadership, operational management, and human resource development by providing empirical evidence on the effectiveness of Blue Ocean Leadership in enhancing productivity within the automotive manufacturing sector.